2019
DOI: 10.1080/20002297.2019.1643207
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and impact of lysogeny among oral isolates ofEnterococcus faecalis

Abstract: Bacterial phenotypic properties are frequently influenced by the uptake of extrachromosomal genetic elements, such as plasmids and bacteriophage genomes. Such modifications can result in enhanced pathogenicity due to toxin production, increased toxin release, altered antigenicity, and resistance to antibiotics. In the case of bacteriophages, the phage genome can stably integrate into the bacterial chromosome as a prophage, to produce a lysogenic cell. Oral enterococcal strains have been isolated from subgingiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…faecalis could be attributed to both aggregation substance (Asa) and methionine sulfoxide reductase (Msr) encoded by the φEf-vB1 prophage [42, 72]. In support of the current findings, previous studies have reported that biofilm production by bacteria is significantly promoted in the presence of prophages [50, 73–75]. Stevens et al demonstrated that enhanced biofilm formation by lysogenic E.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…faecalis could be attributed to both aggregation substance (Asa) and methionine sulfoxide reductase (Msr) encoded by the φEf-vB1 prophage [42, 72]. In support of the current findings, previous studies have reported that biofilm production by bacteria is significantly promoted in the presence of prophages [50, 73–75]. Stevens et al demonstrated that enhanced biofilm formation by lysogenic E.…”
Section: Discussionsupporting
confidence: 82%
“…faecalis and there is not much data available on the acquisition of phage genomic information by E. faecalis [50]. Importantly, many studies have reported that lysogeny has been demonstrated in E.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oral cavity also hosts phages of pathogenic invaders (eg, E. coli, Pseudomonas aeruginosa, Staphylococcus aureus, Enterococcus faecalis) and Lactobacillus phages that can be found in environments other than the oral cavity. [115][116][117][118][119][120][121] No phages of the phyla Absconditabacteria (formerly known as SR1), Chlamydiae, or…”
Section: 108mentioning
confidence: 99%
“…In Gram-positive bacteria, the cell wall is the outermost component and purified endolysins can instantly kill the bacteria upon contact when added to the culture. Endolysins from E. faecalis phages have been previously purified and characterized a number of times [ 18 , 19 , 20 , 21 ]. Biochemical activity, as well as in vivo efficacy [ 18 ], was observed.…”
Section: Introductionmentioning
confidence: 99%